Algorithmic and software of migration of databases in hypermarket network - Mruts, Volodymyr; Mashevska, Marta (Lviv Politechnic Publishing House, 2020)
Possible ways and options of migrating data from existing database management systems to new ones have been analyzed in the article. Also, the main advantages and disadvantages of these methods have been considered, the common problems that may arise during migration and the standard requirements for thistype of system have been given. In the practical part, the Exact Transform Load (ETL) system has been developed with the implementation of all its functional and non-functional requirements, migrating data from the old system to the new one.
Keywords: data migration, automation, Exact Transform Load (ETL), transformation